Association of Auroral Streamers and Bursty Bulk Flows During Different States of the Magnetotail: A Case Study. Issue 9 (27th September 2021) - Ferdousi, Banafsheh; Raeder, Joachim; Zesta, Eftyhia; Cramer, William; Murphy, Kyle
Abstract: In‐situ measurements in the magnetotail are sparse and limited to single points. On the other hand, there is a broad range of observations, including magnetometers, aurora imagers, and radars, in the ionosphere. Since the nightside ionosphere resembles the magnetotail plasma sheet dynamics projection, it can be used to monitor the tail's dynamics. A proper interpretation of the ionosphere and ground observations necessitates understanding the coupling processes between the ionosphere and the magnetosphere. Here, we use the global magnetohydrodynamic simulation model, OpenGGCM‐CTIM‐RCM, to investigate these coupling processes during periods when the magnetic flux is transported through the tail via narrow fast flow channels, typically called bursty bulk flows (BBFs). We consider three relevant states of the magnetotail: immediately before the substorm's onset, during the expansion of the substorm, and during a steady magnetic convection (SMC) event. The number of flow channels increases, and they penetrate closer to the Earth during SMC. The IMF B y direction influences fast flows' location but not their orientation in the plasma sheet during this event. However, the dimension of fast flows and streamers do not depend on the IMF conditions and state of the magnetosphere. Key Points: Mapped fast flows from the magnetosphere to the ionosphere resemble auroral streamers in the simulation The number of fast flows and streamer increases during substorm expansion and SMC, and they penetrate closer to the Earth during SMC The location of BBFs is controlled by the state of the magnetosphere and interplanetary magnetic field (IMF) B y